Nurses’ Experiences in Implementing Patient Safety Programs in Inpatient Settings: A Qualitative Study - Arruum, Diah; Setyowati, Setyowati; Handiyani, Hanny; Artono Koestoer, Raldi (Nurse Media Journal of Nursing, 2026)
Background: Patient safety is a fundamental aspect of healthcare in hospital settings; however, implementing it remains challenging in nursing practice due to factors such as inadequate staffing, heavy workloads, poor communication, and limited resources. While previous studies have primarily focused on these structural and organizational barriers, there is limited understanding of nurses’ experiences in implementing patient safety programs, particularly in inpatient settings.Purpose: This study aimed to explore nurses’ experiences in implementing patient safety programs in hospital inpatient settings.Methods: A descriptive qualitative study was conducted among 22 ward nurses selected using purposive sampling. The inclusion criteria were nurses with at least one year of work experience and a minimum of a bachelor’s degree in nursing or equivalent professional nursing qualifications. Data were collected through focus group discussions (FGDs) and analyzed using thematic analysis.Results: Four main themes were identified: (1) understanding patient safety principles, (2) barriers to patient safety implementation, (3) leadership and organizational support for patient safety, and (4) technology as a facilitator of patient safety. Although nurses demonstrated an understanding of patient safety principles, they continued to encounter barriers, including variations in peer awareness of safety standards, workload constraints, and a blame culture. Furthermore, nurses reported anxiety and demotivation when reporting errors, highlighting the need for stronger leadership and organizational support. Finally, participants emphasized technology’s role as a key facilitator in achieving patient safety goals.Conclusion: Nurses’ commitment, patient safety–related workplace culture, and the availability of innovative technology remain critical factors influencing the implementation of patient safety programs. Communication barriers, limited managerial support, and challenges in sustaining patient safety practices persist. Therefore, hospital leadership should strengthen systems and policies, improve resource planning, enhance support and supervision, and provide continuous training to improve patient safety programs.